THE INDONESIA DEFENSE DIPLOMACY TO SPAIN YEAR 2014-2018 TOWARD THE COOPERATION IN THE FULFILMENT OF DEFENSE AND SECURITY EQUIPMENT - Khory Wandira Ambarsari; Sutrimo Sumarlan; Herly Dwiyanto (The Republic of Indonesia Defense University, 2021)
Indonesia and Spain have established diplomatic relations since 1958, mainly in the defense sector. However, in its implementation, several problems occur, are the budget limitation, the financial crisis in Spain, the lack of human and technological resources in Indonesia, and the presence of assembly problems on CN-295. This study aims to analyze the form of defense diplomacy that occurred and the results of cooperation in fulfilling defense and security equipment in 2014-2018. The study uses a qualitative approach with a case study in analyzing research. The results obtained show that the implementation of defense diplomacy carried out by Indonesia and Spain in 2014-2018 has been going well, proved by the bilateral dialogue forum, activities of visiting state officials, the production of nine units of CN-295 and KRI Bima Suci as defense weapon system products, and an exchange of military students to create a stronger national defense.